The significance of pre-arrest factors in out-of-hospital cardiac arrests witnessed by emergency medical services: A report from the Victorian Ambulance Cardiac Arrest Registry - Nehme, Z.; Andrew, E.; Bray, Janet; Cameron, P.; Bernard, S.; Meredith, I.; Smith, K. (2015)
© 2014. Background: The significance of pre-arrest factors in out-of-hospital cardiac arrests (OHCA) witnessed by emergency medical services (EMS) is not well established. The purpose of this study was to assess the association between prodromal symptoms and pre-arrest clinical observations on the arresting rhythm and survival in EMS witnessed OHCA. Methods: Between 1st January 2003 and 31st December 2011, 1056 adult EMS witnessed arrests of a presumed cardiac aetiology were identified from the Victorian Ambulance Cardiac Arrest Registry. Pre-arrest prodromal features and clinical characteristics were extracted from the patient care record. Backward elimination logistic regression was used to identify pre-arrest factors associated with an initial shockable rhythm and survival to hospital discharge. Results: The median age was 73.0 years, 690 (65.3%) were male, and the rhythm of arrest was shockable in 465 (44.0%) cases. The most commonly reported prodromal symptoms prior to arrest were chest pain (48.8%), dyspnoea (41.8%) and altered consciousness (37.8%). An unrecordable systolic blood pressure was observed in 34.4%, a respiratory rate <13 or >24min-1 was present in 43.1%, and 45.5% had a Glasgow coma score <15. In the multivariable analysis, the following pre-arrest factors were significantly associated with survival: age, public location, aged care facility, chest pain, arm or shoulder pain, dyspnoea, dizziness, vomiting, ventricular tachycardia, pulse rate, systolic blood pressure, respiratory rate, Glasgow coma score, aspirin and inotrope administration. Conclusion: Pre-arrest factors are strongly associated with the arresting rhythm and survival following EMS witnessed OHCA. Potential opportunities to improve outcomes exist by way of early recognition and management of patients at risk of OHCA.